Virginia Woolf and nineteenth-century women writers : Victorian legacies and literary afterlives - Reus, Anne (Edinburgh University Press, 2022)
This book examines Virginia Woolf's influence on the literary afterlives of nineteenth-century women of letters including Jane Austen, Mary Russell Mitford, Elizabeth Barrett Browning, Charlotte Brontë, George Eliot, Margaret Oliphant and Mary Augusta Ward through her journalism. Woolf's responses to her literary predecessors provide new insights into her self-positioning within the literary canon and the interplay of biographical innovation and Victorian legacies in her non-fiction. This study demonstrates that Victorian narratives and tropes of female professionalism continue to shape Woolf's representations of nineteenth-century women writers even at the heyday of her Modernist fame. It contextualizes the overt feminism of A Room of One's Own within Woolf's more ambiguous literary biography to argue for its status as a transitional, post-Victorian body of work.